Análisis del uso de plaguicidas químicos en el tomate riñón (solanum lycopersicum l) producido a campo abierto e invernadero en la periferia de la ciudad de Loja - Castillo Pérez, Bernardo Gonzalo (2021)
The objectives of this research were to identify and characterize the chemical pesticides used in the production management of kidney tomatoes, both in greenhouses and in open fields on the outskirts of the city of Loja. The use of agrochemicals is a frequent practice in the production of this vegetable; lack of knowledge and the idiosyncrasy itself causes the inappropriate use of these chemicals, affecting the safety of the product and consequently affecting the health of producers, consumers and the environment in general. Field evaluations showed that the use of agrochemicals is mostly done empirically, ignoring basic aspects such as the use of recommended doses indicated in the technical data sheets or the use of protective equipment during spraying. The characterization determined that the three modes of action most frequently found in insecticides are those that act on the nervous and muscular systems and on growth regulation, while the mode of action most frequently found in fungicides are those that have multi-site action on metabolic processes. During spraying, these chemicals are mixed and applied without any technical criteria, which can lead to overdosing or adverse chemical reactions, and it was also observed that the re-entry periods are not respected and the periods of lack of fumigated chemicals are not clear. The conclusion of this study is that it is essential to issue regulations that can be applied in the province of Loja for the use and management of pesticides and also to maintain permanent monitoring of the use of these chemicals in the province's agricultural crops.